Evaluation of increasing antecedent specificity in goal statements on adherence to positive behavior‐management strategies. Issue 4 (26th May 2016) - Cohrs, Corey M.; Shriver, Mark D.; Burke, Raymond V.; Allen, Keith D.
Abstract : We evaluated the impact of antecedent specificity in goal statements on adherence to positive behavior‐management strategies. Teaching staff were recruited from 2 different school settings where there were routine expectations to use behavior‐specific praise in the classroom, but adherence was poor. In a concurrent multiple baseline design, the use of behavior‐specific praise by 4 participants was found to be unaffected by goal statements that increasingly specified the behavior to be used and the conditions under which the behavior should occur. However, adherence by 3 of the 4 participants did change when goal statements included teacher‐specified frequencies with which the behavior should occur. Results were systematically replicated in a second study in which, in a concurrent multiple baseline design, 3 participants showed marked increases in adherence when goal statements specified the target behavior, the conditions under which it should occur, and the frequency with which it should occur.